This equation could be solved in many ways.

One way is to notice that the given equation is a difference of two squares that returns the special products:

`25x^2 - 36 = (5x - 6)(5x + 6)`

We'll re-write the equation:

`(5x - 6)(5x + 6) = 0`

We'll cancel each factor and we'll get:

`5x - 6 = 0`

`5x = 6`

`x = 6/5`

`5x + 6 = 0`

`5x = -6`

`x = -6/5`

Another way to solve this equation is to add 36 both sides:

`25x^2 = 36`

We'll divide both sides by 25:

`x^2 = 36/25`

`x_(1,2) = +-sqrt(36/25)`

`x_(1,2) = +-6/5`

**Any method you chose to solve, you'll get the solutions of the equation **`x_1 = 6/5 and x_2 = -6/5.`

25x^2-36=0

>You move -36 to the right, we have:

25x^2=36

>Divide both sides by 25, we have:

x^2 = 36/25

>Take the square root of x^ 2 to solve for x:

√x^2 = √36/25

x ± 6/5

Hope I helped......